Diverse environmental bacteria displaying activity against Phakopsora pachyrhizi, the cause of soybean rust - Twizeyimana, Mathias; Hammer, Philip E.; Gachango, Esther; Craig, Kelly; Espejo, Billie; Biggs, Matthew B.; Kremer, James; Ingham, David J. (Frontiers in Plant Science, 2023)
The management of soybean rust (SBR) caused by the obligate fungus Phakopsora pachyrhizi mostly relies on the use of synthetic fungicides, especially in areas where the disease inflicts serious yield losses. The reliance on synthetic fungicides to manage this disease has resulted in resistance of P. pachyrhizi populations to most fungicides. In this study, bacteria isolated from diverse environments were evaluated for their biocontrol potential against P. pachyrhizi using soybean detached-leaf method and on-plant in the growth chamber, greenhouse, and field. Among 998 bacterial isolates evaluated using the detached-leaf method; 58% were isolated from plant-related materials, 27% from soil, 10% from insects, and 5% from other environments. Of the isolates screened, 73 were active (they had ⋝ 75% rust reduction) with an active rate of 7.3%. From the active isolates, 65 isolates were re-tested on-plant in the growth chamber for activity confirmation. In the confirmation test, 49 bacteria isolated from plant-related materials maintained their activity with a confirmation rate of 75%. The majority of bacteria with confirmed activity belonged to the taxonomic classes Bacilli and Gammaproteobacteria (70%). Active isolates were prioritized for greenhouse and field testing based on activity in the initial screen and confirmation test. Six bacterial isolates AFS000009 (Pseudomonas_E chlororaphis), AFS032321 (Bacillus subtilis), AFS042929 (Bacillus_C megaterium), AFS065981 (Bacillus_X simplex_A), AFS090698 (Bacillus_A thuringiensis_S), and AFS097295 (Bacillus_A toyonensis) were selected from those bacteria that maintained activity in the confirmation test and were evaluated in the greenhouse, and five among them were evaluated in the field. From the Alabama field evaluation, all bacterial isolates reduced rust infection as well as azoxystrobin (Quadris® at 0.3 L/ha) used as the fungicide control (P > 0.05). Moreover, the scanning electron micrographs demonstrated evidence of antagonistic activity of AFS000009 and AFS032321 against P. pachyrhizi urediniospores. Bacterial isolates that consistently showed activity comparable to that of azoxystrobin can be improved through fermentation and formulation optimization, developed, and deployed. These bacteria strains would provide a valuable alternative to the synthetic fungicides and could play a useful role in integrated disease management programs for this disease.